Mixed-Mode Bacterial Transmission via Eggshells in an Oviparous Reptile Without Parental Care - Li, Teng; Yang, Yang; Li, Huijun; Li, Chunkai (Frontiers in Microbiology, 2022)
Symbiotic microorganisms play important roles in maintaining health and facilitating the adaptation of the host. We know little about the origin and transgenerational transmission of symbiotic bacteria, especially in egg-laying species without parental care. Here, we investigated the transmission of bacterial symbionts in the Chinese three-keeled pond turtle (Mauremys reevesii), a species with no post-oviposition parental care, by evaluating contributions from potential maternal and environmental sources to eggshell bacterial communities. Using 16S rRNA amplicon sequencing, we established that the bacterial communities of eggshells were similar to those of the maternal cloaca, maternal skin, and nest soil, but distinct from those of surface soil around nest and pond water. Phylogenetic structure analysis and source-tracking models revealed the deterministic assembly process of eggshell microbiota and high contributions of the maternal cloaca, maternal skin, and nest soil microbiota to eggshell bacterial communities. Moreover, maternal cloaca showed divergent contribution to eggshell microbiota compared with two other main sources in phylogenesis and taxonomic composition. The results demonstrate a mixture of horizontal and vertical transmission of symbiotic bacteria across generations in an oviparous turtle without parental care and provide insight into the significance of the eggshell microbiome in embryo development.